Ground improvement using chemical methods: A review. Issue 7 (July 2021) - Verma, Harshal; Ray, Arunava; Rai, Rajesh; Gupta, Tushar; Mehta, Neeraj
Abstract: Ground improvement will be critically important in the present and future geotechnical practice for designing the structures in weak soil. This paper presents a review of the recent development in ground improvement techniques, especially chemical stabilisers. Various available chemical stabilisers are identified and compared with other available methods. Though the use of chemicals provides an excellent alternative to the traditional methods, they still lack proper understanding regarding their use, handling, application, and long-term effect on the environment. Various chemical stabilisers and their applicability conditions are summarised in the present paper. Insight of biochemical, electrochemical, inorganic, and organic stabilisers is presented with future scope of these methods along with the potential areas where a lot of efforts is needed to industrialise these methods are also discussed briefly. A need for developing a more environmentally friendly and safe method was felt while reviewing these methods. Lack of a large amount of data is a major concern for lesser use of these methods industrially. A lot of laboratory and field experiments should be conducted in different conditions to ensure safe results from chemical stabilisers. Abstract : Ground improvement; Chemical stabilisers; Biochemical stabilisers; Electrochemical stabilisers; Inorganic and organic stabilisers.